Cruising utopia the then and there of queer futurity - Muñoz, José Esteban 1967-2013 (New York University Press, 2019)
"Cruising Utopia arrived in 2009 to insist that queerness must be reimagined as a futurity-bound phenomenon, an insistence on the potentiality of another world that would crack open the pragmatic present. Part manifesto, part love-letter to the past and the future, Jose Esteban Munoz argued that the here and now were not enough and issued an urgent call for the revivification of the queer political imagination." - Verlag
Keywords: Queer-Theorie; Performance -- Künste; Kunst; Homosexualität; Utopie